(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This article examines the social and economic reforms implemented by the central government in the rural areas of Kashkadarya region. The study analyzes the impact of the policy of kulakization and collectivization on the lives of the population, the conflicts between social strata, and how they were reflected in the local way of life. It also highlights the social relations and ideas that emerged in the minds of the population as a result of such processes as the reduction of individual peasant farms, the distribution of large landowners and private land. The content of the study is aimed at analyzing the complex impact of socio-economic changes on rural life from a scientific perspective.